Pendidikan Ibadah dalam Al Qur’an - Predi Ari Repi; Asnil Aidah Ritonga; Mohammad Al Farabi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The point of the article is to get it revere instruction within the Koran, what is instruction, what is adore. and in verses that incorporate revere. Instruction is an instructive movement that's carried out in a develop, genuine and modified arrange. All activities performed by somebody who is cherished and favored by Allah are said to be revere. Writing. This is often a concept examination employing a subjective expressive approach. Within the world of instruction, it is evident that the administration and execution of instruction must be pointed at increasing awareness and acknowledgment of the part of people as workers of God, specifically revere. It is trusted that the open will get it that giving instruction may be a way of worshiping Allah.